Joel und Ethan Coen: Meister der Überraschung und des vielschichtigen Humors - Zeul, Mechthild (transcript, 2016)
On the psychology of the Coen brothers – and on their films that combine cruelty, empathy, and humor, holding a mirror up to social and political life in the USA.